Pemberdayaan Masyarakat Berbasis Multikultural di Majelis Taklim An Najach Magelang - Imamul Huda (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2019)
This research aims to describe the lecture of An Najach majelis taklim and its function for people empowerment activities. The research method uses qualitative-descriptive methods through the interview, observation, and documentation. The place of the research is at An Najach majelis taklim located in An Najach Islamic boarding school in Magelang. The results showed that first, the lecture materials are normative, emphasizing individual piety and not prioritizing issues related to living together in pluralism and multiculturalism; second, in addition to multicultural values, religious lectures contain some anti-multicultural values, such as truth claims, prejudices, stereotypes against other groups, stigma and judgment, and hate speech; and third, An Najach represents the capable majelis taklim to empower people in the spiritual, economic, educational, and social aspects. This research recommends the importance of professionalism in managing majelis taklim and good communication with the audience and people. This research enriches studies on the development of Islamic societies, especially in people empowerment based on majelis taklim.